Evaluasi Kualitas Website PoliceTube dengan WebQual 4.0 - Ammar Shafiy; Nova Tri Romadloni (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
This study examines the quality of PoliceTube.com from users' perspective using the WebQual 4.0 framework. This framework covers three dimensions — Usability Quality, Information Quality, and Service Interaction Quality — which were examined to determine which has the most influence on users' overall assessment. Data were collected via online questionnaire from 50 PoliceTube.com visitors selected through purposive sampling and analyzed using SPSS 26 through validity, reliability, Pearson correlation, and multiple linear regression tests. The instrument proved reliable with a Cronbach's Alpha of 0.877. All three WebQual dimensions positively correlated with Overall Quality, with Usability Quality being the strongest (r=0.502). The R Square value of 0.696 indicates that approximately 70% of the variation in overall quality assessment is explained by the three WebQual 4.0 dimensions. Notably, only the usability dimension had a significant individual impact based on partial testing. This suggests that PoliceTube.com visitors prioritize navigation ease and interface comfort over other aspects when assessing website quality. Therefore, administrators should focus on improving page layout, navigation clarity, and display consistency. Future research is recommended to expand the sample size and include additional variables such as user trust, content quality, or security perception for more comprehensive results.